Polypharmacy in Psychiatry Practice, Volume I Multiple Medication Use Strategies - Ritsner, Michael S. (Springer Netherlands : Imprint: Springer, 2013)
Despite the large number of psychotropic medications currently available, effective management of mental disorders continues to be a challenging task. Although monotherapy may be desirable, most patients require combinations of two or more psychotropic drugs. Polypharmacy aims to address different aspects of treatment resistance, especially insufficient response of positive and negative symptoms, cognitive disturbances, affective comorbidity, obsessive-compulsive syndromes and side-effects of antipsychotic agents. At the same time, evidence based guidelines in support of polypharmacy, and augmentative strategies are scant. This two-volume collection is the first comprehensive, clinically oriented, reference text on polypharmacy (co-administration of more than one medication) or the use of multiple preparations to treat psychotic, cognitive, mood and anxiety disorders. This collection is divided into four parts. Volume I contains two parts including chapters that serve as an introduction and overview of conceptual issues. Key topics include: rational polypharmacy, receptor binding targets, drug interactions, preclinical and clinical investigations in this field, dosing regimens, multiple medication use in forensic psychiatry, a naturalistic trial, adjunctive strategies, and multiple medication use for the treatment of somatic symptom disorders. Volume II contains two parts that focus on antipsychotic polypharmacy for schizophrenia, and clinical practice in the USA, Czech Republic, Ukraine, and Italy, polypharmacy and associated phenomena, clozapine combinations and the metabolic syndrome. The authors discuss combination therapy for bipolar disorder, major depressive disorder, obsessive-compulsive syndromes in schizophrenia, and potentially inappropriate medication use among elderly patients with dementia. Finally, each volume includes Appendix contains 'Annotated bibliography on polypharmacy' and 'List of Psychotropic Medications'.